The Relationship of Mass Behavior to Sports Perception among Soccer Players - Hamad Lahmood Taherh; Addul abbas Abdulrazaq (Indian Journal of Forensic Medicine & Toxicology, 2021)
Sports activity is highly dependent on behavior that greatly affects the level of activity and the result and thisaspect is related to the amount of awareness that the player possesses during his public and private culture.The research aims to know the relationship between these variables among football players. The amount ofculture that players have reached during their athletic careers.